(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
The stratigraphy of latest Arnsbergian to early Chokierian (Serpukhovian/Bashkirian) is described for the Barcaliente Formation in the Cantabrian Mountains. The conodont content has been studied at the Millaró section, where the appearance of Declinognathodus noduliferus Ellison & Graves, in the lower metres of the Barcaliente Formation is confirmed, and the location of the Mississippian/Pennsylvanian boundary is discussed. The new subspecies D. noduliferus bernesgae is described and other records are also studied from the Pyrenean Azkarate section. First occurrences of Declinognathodus species are discussed from different basins, and a sequence of first appearances is applied for world-wide correlation. The lowest occurrence of D. inaequalis at the Mid-Carboniferous boundary GSSP is preferred as the primary correlation marker, because D. noduliferus s.l. includes several different taxa. Gnathodus and Lochriea species persist above the base of the Pennsylvanian and disappear in the Chokierian (early Bashkirian), as described elsewhere.